Meaning of The Symbol of The Mulutna Figure in Sukuraga Puppet - Aulia, Regina Putri (PT. Alahyan Publisher Sukabumi, 2023)
The content of the discussion is about puppet, symbol, and the meaning in one of the figure in the puppet. Puppet is one of the traditional 2-dimensional entertainment media, which can be seen and also felt. A puppet always contains a message in it related to the conditions of life in the world that we live. In West Java, especially in Sukabumi, there is a Sukuraga puppet created by an extraordinary artist named Effendi. Mr. Effendi created Sukuraga puppet, where this Sukuraga means